Back flashover mitigation for transmission tower by parallel additional multiple conductors from tower top to ground footage to alter the surge impedance - Chakkri Satchathampitak; Rongrit Chatthaworn; Amnart Suksri (Energy Reports, 2022)
This research assessed the transmission tower’s surge impedance before and after paralleling the overhead ground wire (OHGW) made of twisted galvanized steel cable from topmost of the transmission tower to the tower ground footage. Laboratory scale lightning current impulse generator of 5 kA 8/20 μs lightning waveform was applied at topmost of the laboratory scale transmission tower. The height of the constructed transmission tower is 1.96 m, and the width of the transmission tower is 0.42 m. When the impulse current was applied, consideration parameters for estimating transmission tower’s surge impedance are the voltage and current obtained from each cross-arm. The value of surge impedance can be calculated form measurement using impulse voltage divider and Rogowski coil for lightning impulse current at the tower. The result of the surge impedance of the entire transmission tower before connecting the conductors is 91.58 Ω. When paralleling the OHGW conductors from 1 to 4 wires, transmission tower surge impedance is changed. When paralleling one conductor, the surge impedance of the laboratory scale transmission tower is 70.00 Ω. When two conductors were paralleled, the tower surge impedance value is 63.75 Ω. When three conductors are paralleled, the tower surge impedance is 62.50 Ω. And when four conductors were paralleled, the surge impedance is further reduced to 61.25 Ω. Therefore, by paralleling multiple conductors using this method, transmission tower’s surge impedance was able to reduce due to more current pathway via additional OHGW. Also, the voltage that appears at each cross-arm of the transmission tower was reduced and thus, lowering the back flashover phenomena.